The Postmodern Reception of Maurycy Straszewski’s Religious Explorations - Guzowska, Beata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2025)
Contemporary developments in the area of religion and religiosity have been significantly influenced by the processes of modernisation, secularisation and universal pluralism. In the ideas of many postmodern philosophers, the concept of the “return of religion” appears. This concept was presented, among others, by Maurycy Straszewski, whose thought stems from 19th-century positivism. Many elements of Straszewski’s theory are represented in contemporary philosophical statements on the transformation of religiosity. Particularly important are the postulate of the compatibility of religion with reason and science, the departure from dogma, the individualisation of spirituality, and the influence of religion on the formation of moral attitudes, social relations and interpersonal solidarity.

Współczesne przemiany w obszarze religii i religijności zostały znacząco ukształtowane przez procesy modernizacji, sekularyzacji i powszechnego pluralizmu. W koncepcjach wielu filozofów postmodernistycznych pojawia się idea „powrotu religii”. Koncepcję tę przedstawił m.in. Maurycy Straszewski, którego myśl wywodzi się z XIX-wiecznego pozytywizmu. Wiele elementów jego teorii znajduje swoje odzwierciedlenie we współczesnych wypowiedziach filozoficznych na temat przemian religijności. Szczególnie istotne są postulat zgodności religii z rozumem i nauką, odejście od dogmatów, indywidualizacja duchowości oraz wpływ religii na kształtowanie postaw moralnych, relacji społecznych i solidarności międzyludzkiej.
Postmodernistyczna recepcja religijnych eksploracji Maurycego Straszewskiego
Keywords: contemporary culture; religion; transcendence; postmodernity; Straszewski; kultura współczesna; religia; transcendencja; ponowoczesność